Women and Nature in BP Koirala’s Sumnima: An Ecofeminist Study - Mishra, Indira Acharya (Dristikon: A Multidisciplinary Journal, 2020)
The article aims to analyze the connections between women and nature in Bisheshwar Parsad Koirala's novel Sumnima. To examine the relation between women and nature in the novel, the theory of eco feminism has been used. Eco feminism deals with the relationships between women and nature that particularly deals with the domination of women and exploitation of nature in a patriarchal social order. Eco feminist critics believe that issues of women and ecology are interrelated. They critique that the domination of nature by human beings is guided by the patriarchal world view, the same world view that justifies the domination of women. Thus, they resist the exploitation of women and nature. Koirala's Sumnima underscores the patriarchal structure based on dualisms like men/woman, masculine/ feminine, culture/nature, and spiritual/material, which destabilizes the system based on the hierarchy of the traditional gender roles. Thus, the article argues that the novel is written from the perspective of eco feminism. The analysis of the study centers on the depiction of women and nature in the novel. The finding of the article shows that, in patriarchy, women and nature are treated as feminine and they are dominated and exploited. The analysis is significant as it helps to understand the importance of feminine to maintain harmonious relation between men, women and nature.